The Internet of Products An Approach to Establishing Total Transparency in Electronic Markets - Neumann, Robert; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2013)
This text approaches the difficult problem of providing Internet users with a completely transparent view on electronic markets from a product information accessibility point of view. Robert Neumann analyzes economic, ecological, and societal gains of openly accessible product information in the form of theoretical models. Though many aspects of very different research disciplines have to be investigated to gain a holistic view on the Internet of Products, this text reduces the range of involved research topics to product information discoverability related questions. Contents The Econmics of E-Economics, The Internet of Products and the Triple Bottom Line, Semantic Product Description Language, Semantic Product Servers. Target Groups Researchers and students in the field of IT and business IT, Managers and experts with focus on Semantic Web, E-Commerce, Semantic Product Search. About the Author Robert Neumann is currently working as a researcher at the Department of Distributed Systems at the Otto-von-Guericke University in Magdeburg, Germany. His focus is upon the design and implementation of new Internet usage scenarios.
The Economics of E-Economies -- E-Commerce Process Modeling -- The Internet of Products and the Triple Bottom Line -- Foundations of Semantic Product Query Systems -- Semantic Product Description Language -- Semantic Product Servers.
Keywords: Computer science; Computer Science; e-Commerce/e-business.